Epilepsy with hallucinatory phenomena in pediatric age: a case report - Rodrigues, Marlene (2016)
Introduction: Hallucinations in children may be part of normal development and not necessarily a symptom of mental illness, but they are subject of great concern to parents and clinicians. They may be a manifestation of a wide spectrum of disorders, such as intoxication, acute febrile illness, endocrinological, neurological or psychiatric disorder. Case Report: Clinical report of a previously healthy nine-year-old boy presented with visual and auditory hallucinations over the last month. During hospitalization it was performed electroencephalogram, audio record of hallucinatory description and child's illustration of the goblins seen in hallucinations. The etiological investigation excludes other causes, and changes in the electroencephalogram confirmed the diagnosis of epilepsy. The child presented with clinical improvement after treatment with sodium valproate, without recurrence of symptoms. Conclusion: This clinical report intended to emphasize the importance of considering epilepsy as a differential diagnosis in children and adolescents with psychic phenomenology, to make a timely diagnosis and treatment.